Algorithm aspects of Rubik’s Cube 3D game - Subaramya, V.; Krishnakumar, K. (The Open University of Sri Lanka, 2013)
The Rubik's Cube is really captivating and fascinating puzzle. It is a 3D game. In the literary survey, there are several applications available in Rubik’s cube. Some of them are games, some of them have solution. But there are no applications which guide how to solve Rubik’s cube. This application is very useful to study about solving the Rubik’s cube. User can play the Rubik’s Cube by turning 12 sides. No of Turns and the time of play will calculate. When User solved the cube there will be a Congratulation Message will be shown with the no of turns and Time. If the user is not familiar with solving cube, they can get the automatic solution which will give the steps to solve the cube. To solve the cube there are five steps. First take the edge pieces of the top layer then the corner pieces of the top layer. The third step is the edge pieces of the middle layer. Then the corner & edge pieces of the bottom layer. When user gets the solution it will give the total no of steps and user can do the next & previous or can auto solve. When going through the steps, it will give the step number, step description & turn Description. In the Right side of the Application, it will give the help file according to the step Number. So user can refer the help file & the steps. So this will be an easy guide for them to learn Rubik’s Cube.
Keywords: Fascinating puzzle; Algorithm